2013
DOI: 10.1037/a0031433
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among female inmates with bipolar disorder: Results from a randomized controlled trial.

Abstract: To describe the differences in medication adherence between 2 groups of inmates in the Connecticut Department of Correction diagnosed with bipolar disorder treated with either the Texas Implementation of Medication Algorithm (TIMA) for Bipolar Disorder or treatment as usual (TAU). Using a prospective longitudinal analysis of secondary data and chart data, a comparison was made between participants who were assigned either to TIMA or TAU and treated for 12 weeks for either Bipolar Disorder Type I or II. A secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We found that the majority of participants had poor medication adherence, while age, sex, education level, duration, and number of medications were not found to be correlated with medication adherence. Previous studies have reported inconsistent results between demographic variables and medication adherence, 23,[28][29][30] while some support age, sex, number of medications, and medical conditions being independent predicators of medication adherence. 23,30,31 In line with our study, a study conducted in China also reported that education level was the only predicator of medication adherence, 27 while another study reported that age was the only factor that correlated with medication adherence among Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of participants had poor medication adherence, while age, sex, education level, duration, and number of medications were not found to be correlated with medication adherence. Previous studies have reported inconsistent results between demographic variables and medication adherence, 23,[28][29][30] while some support age, sex, number of medications, and medical conditions being independent predicators of medication adherence. 23,30,31 In line with our study, a study conducted in China also reported that education level was the only predicator of medication adherence, 27 while another study reported that age was the only factor that correlated with medication adherence among Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Work with other medications is limited. Another study found that, in women with bipolar disorder, following an evidence-based pharmacological treatment algorithm was no better than treatment as usual (where medication decisions were taken by the treating clinician)48 for reducing symptoms and improving medication adherence. More psychopharmacology research in prison settings is required, particularly for commonly prescribed psychotropic medications (see Research Recommendations).…”
Section: Interventionsmentioning
confidence: 99%
“…50-53,57-59, 81,82,90,132 High-dose valproic acid treatment compared with low-dose treatment led to less illness severity in adolescent boys with conduct disorder. 132 In adult women with bipolar disease, the use of an algorithm for the treatment of bipolar disease improved medication utilization and adherence compared with usual care.…”
Section: Mental Health Interventionsmentioning
confidence: 99%
“…Adult women with bipolar type I or II Texas Implementation of medication algorithm for bipolar disease vs treatment as usual 81,82 Mental health Adolescent boys with posttraumatic stress disorder Short-term cognitive processing therapy vs no intervention 68 Mental health…”
Section: Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation